(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2022)
Confucianism is a worldview that has shaped Chinese civilization and its various forms of statehood for over two thousand years. With the establishment of the People’s Republic of China in 1949, its influence on the shaping of ideology and social life was interrupted for several decades. The new direction of the state initiated at the end of the 1970s resulted in the gradual restoration of selected ideas of Confucianism, which, along with Marxism and the strategy of entering globalization, shape the international identity of the Middle Kingdom. While Marxism remains the official ideology, one should focus on introducing elements of Chinese culture, which complements it in recognizing contemporary realities and formulating directions for changes in the state. The aim of the article is to show the influence of Confucianism on the contemporary Chinese narrative manifested in two dimensions: internal affairs, i.e. the development of the state and society, and external issues, international politics.